DEMOCRACY AND ETHNIC CONTESTATIONS IN NIGERIA: ISSUES AND CASES - OKPATA, Fidelis O; EZIKA, Goodness A (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Nigerian democracy has suffered serious lack of democratic consolidation and not to talk about sustainable development. Many factors have been adduced as responsible for this, particularly the plural nature of our political system which has engendered ethnic politics; with its attendant ethnic contestations. This paper is aimed at identifying the various issues that have challenged democratic consolidation in Nigeria amongst the ethnic nationalities, with the purpose to advance possible panacea for sustainable democratic development in Nigeria. The paper relied heavily on secondary data and adopted ethnic-political identity theory and group theory as models of theoretical analysis. The paper found that politics of ethnic marginalization, resource control and allocation, political exclusion, corruption and fraud together with leadership ineptitude, promote ethnic contestations in Nigeria. The paper finally recommended for political and economic restructuring, regional autonomy and inclusive politics in the democratic governance of Nigerian State.